Risk Factor Analysis of Maternal Compliance in Polio Immunization for Toddlers: An Observational Study in Padang Pariaman, Indonesia - Tyas, Dina Ayuning; Ira Maulina Sa’danoer; Meli Sundari (Archives of The Medicine and Case Reports, 2024)
Polio remains a significant global health concern, with maternal compliance in immunization programs playing a crucial role in eradication efforts. This study aimed to identify risk factors associated with maternal compliance with polio immunization for toddlers in Padang Pariaman, Indonesia. A cross-sectional observational study was conducted among 350 mothers of toddlers (12-23 months) in Padang Pariaman. Data were collected using a structured questionnaire, including socio-demographic characteristics, knowledge and attitudes towards immunization, access to healthcare services, and perceived barriers. Compliance was assessed based on immunization card records and maternal recall. Multivariable logistic regression analysis was employed to identify independent risk factors. The overall compliance rate for polio immunization was 78.3%. Factors significantly associated with non-compliance included lower maternal education level (OR=3.12; 95% CI: 1.85-5.27), lack of knowledge about polio and its immunization (OR=2.65; 95% CI: 1.56-4.49), residing in rural areas (OR=2.08; 95% CI: 1.23-3.51), and perceived barriers to immunization (OR=4.78; 95% CI: 2.85-7.99). Several modifiable risk factors for non-compliance with polio immunization were identified. Targeted interventions addressing maternal education, knowledge enhancement, access to healthcare, and addressing perceived barriers could significantly improve polio immunization coverage in Padang Pariaman and similar settings.